The transformation of ownership policy and structure in Sweden: Convergence towards the Anglo-Saxon model? - Magnus Henrekson; Ulf Jakobsson (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
We investigate the dramatic transformation of ownership policies and ownership structure in Sweden during the postwar period. After WWII, Swedish ownership policies were guided by a socialist vision where the ultimate goal was abolition of private ownership. These policies came to an end in the early 1980s. Since then a large number of Swedish firms have been acquired by foreign owners or merged with foreign firms and the foreign ownership share on the Swedish Stock Exchange has increased rapidly. A central question is whether this fast transformation is merely a logical consequence of current globalization, or whether this tendency has been reinforced by economic policies vis-à-vis the business sector in Sweden. We show that until the late 1980s, Swedish economic policy - aimed at discouraging private wealth accumulation and favoring institutional ownership and debt financing - effectively precipitated the rapid takeover of the Swedish business sector by foreign owners that gained momentum in the 1990s. Policy measures intended to create a system of capitalism without capitalists can be said to have packaged large Swedish corporations in terms of ownership and financing structure, so that foreign takeover was facilitated. The article ends with a discussion as to whether the dramatic change in ownership structure in the Swedish business sector may result in the demise of the old corporatist model of industrial relations, giving way to a new trend towards a liberal market economy of the current Anglo-Saxon variety.
Keywords: M13; N24; O38; P16; 330; Corporatism; Entrepreneurship; Industrial policy; Ownership policy; Ownership structure; Swedish Model; Eigentümerstruktur; Unternehmen; Industriepolitik; Schweden